Effect of statins on serum vitamin D concentrations: a systematic review and meta‐analysis. (13th December 2016) - Mazidi, Mohsen; Rezaie, Peyman; Vatanparast, Hassan; Kengne, Andre Pascal
Abstract: Background: We conducted a systematic review and meta‐analysis to assess the effects of statin therapy on serum vitamin D concentrations. Materials and methods: We searched multiple databases including PubMed, MEDLINE, Web of Science and Google Scholar from inception to May 2016, for studies on the effects of statin treatment on serum vitamin D concentration. Quantitative data synthesis used random‐effects models meta‐analysis, with sensitivity analysis conducted using the leave‐one‐out method. Heterogeneity was quantitatively assessed using the I 2 index. The systematic review's registration number was CRD42016035974. Results: In all, seven of 644 studies met our selection criteria including three randomized controlled trials (RCT), three observational cohort studies and one case–control study. Across RCTs, treatment with statins was associated a significant increase in serum vitamin D concentrations [weighted mean difference (WMD) 2·71 ng/mL, 95% CI 0·19–5·24, I 2 62·1%). Across studies of non‐RCT design, statins treatment was associated with a decrease in vitamin D concentrations (WMD −0·70 ng/mL, 95% CI −1·20 to −0·20, I 2 56·3%). These findings were robust in sensitivity analyses. Conclusions: This meta‐analysis was inconclusive on the effects of statins on vitamin D, with conflicting directions of the effects from interventional and observational studies. The suggested favourable effects from RCTs need to be confirmed in larger studies with extended follow‐up in order to determine the possible health benefits.